Anticipated backward doubly SDEs with generators in stochastic Lipschitz condition. (June 2020) - Xing, Zhuangzhuang; Wei, Lifeng
Abstract: In this paper, we prove the well-posedness of the solutions to anticipated backward doubly SDEs (ABDSDEs for short) with stochastic Lipschitz coefficients, where the generators (drivers) of equations not only rely on the prospective values of the pair of solutions, but also satisfy a certain type of Lipschitz condition. This type of equation has a practical background in financial mathematics.